Design and implementation of switched coil LC‐VCOs in the GHz range using the self‐inductance technique. (27th November 2013) - Cernoia, Federico; Ponton, Davide; Palestri, Pierpaolo; Thurner, Peter; Dalt, Nicola Da; Cecco, Giulio; Selmi, Luca
Summary This paper presents the design and implementation of dual‐band LC‐VCOs in the GHz‐range featuring a switched coil LC‐tank. The proposed design exploits the self‐inductance technique. The design of the coil starts from simple considerations and back‐of‐the‐envelope calculations, then electromagnetic simulations are used to optimize the coil layout. The sizing of the switch and its impact on the VCO performance are addressed as well. The VCOs have been implemented in 65 nm CMOS technology. Good correlation between simulated and measured tuning range and phase noise is obtained for all designs, thus confirming the validity and robustness of the design methodology and coil models. Copyright © 2013 John Wiley & Sons, Ltd.